Debt of honor - Clancy, Tom, 1947-2013 (Clancy, Tom, 1947-2013. Jack Ryan novel., 1994)
Clancy's hero Jack Ryan fights to defend the USA against economic sabotage from the East. Called out of retirement to serve as the new National Security Advisor, Ryan soon realizes that the problems of peace are as complex as those of war.